2010
DOI: 10.2298/sarh1012755v
|View full text |Cite
|
Sign up to set email alerts
|

Orbital dermoid and epidermoid cysts: Case study

Abstract: Before the decision to treat the dermoid and epidermoid cysts operatively, a detailed diagnostic procedure was necessary to be done in order to locate the cyst precisely and determine its size and possible propagation into the surrounding periorbital structures. Apart from cosmetic indications, operative procedures are recommended in the case of cysts with constant progressions, which cause the pressure to the eye lobe, lead to motility disturbances and indirectly compress the optical nerve and branches of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The clinical presentation depends on the location, size, rate of growth, intracranial extension and correlation to adjacent structures. [6] Varied clinical signs range from a mass with lid swelling, ptosis, globe displacement, proptosis to ocular protrusion, ocular dissimilarity, limitation of ocular motility and optic nerve compression syndrome. [123] Ruszkowski et al suggested that deep seated dermoid cysts could be associated with pain due to pressure induced stretch of a related sensory nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation depends on the location, size, rate of growth, intracranial extension and correlation to adjacent structures. [6] Varied clinical signs range from a mass with lid swelling, ptosis, globe displacement, proptosis to ocular protrusion, ocular dissimilarity, limitation of ocular motility and optic nerve compression syndrome. [123] Ruszkowski et al suggested that deep seated dermoid cysts could be associated with pain due to pressure induced stretch of a related sensory nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Mild proptosis compared to the lesion size was present in 5 patients (29.4%) who were more concerned about ocular asymmetry secondary to globe displacement and lid fullness. The fact of their presence early in life can explain this sign as the bony orbit expands with increased volume in a way similar to what happens with deeply seated dermoids [8]. …”
Section: Discussionmentioning
confidence: 99%
“…They can break through the orbital walls into the temporal cavity, sinuses, or even intracranial cavity [7]. They present in a variety of ways depending upon the suture of origin, size, rate of growth, and correlation to adjacent structures [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Parsiyel çıkartılan lezyon; kronik granü-lomatöz inflamasyon, rekürrens veya malignansi riski taşıyabilir (2,3,6,7). Derin yerleşimli kistlerde multidisipliner yaklaşımla, maksillofasiyal cerrah, nöroşirürjiyen ve oftalmolojist ekip çalış-ması yapılması uygundur (2,3,6,7). Progresif derin yerleşimli kistik lezyonu olan olgumuz ilerleyen dönemde intrakranial ve intraorbital bölgeye daha fazla invaze olmasına fırsat vermeden, sol frontoorbital kraniotomi uygulanarak kitle total olarak çıka-rılmıştır.…”
Section: Discussionunclassified